RANKING OF FACTORS AFFECTING THE MOBILIZATION OF BANK RESOURCES USING ANALYTICAL HIERARCHY PROCESS (CASE STUDY: IRANAIN HEKMAT BANK) - Hashemi Dehchi, Majid; Nasirzadeh, Elnaz (International Journal of Management, Innovation & Entrepreneurial Research, 2019)
Purpose: The purpose of this study is to identify and rank the factors affecting the resources mobilization of Iranian Hekmat Bank. Methodology: In this research, six main factors are considered in mobilizing resources and deposits of customers of the bank. The statistical population of this research is senior credits managers of Iranian Hekmat Bank. The ranking of these factors has also been done using Analytical Hierarchy Process (AHP) and Expert Choice Software (ECS). Main Findings: The results of this study showed that the factor of loyalty and organizational affiliation has the most impact on resources mobilization. Afterwards, communications and human factors, financial factors, advisory factors, service factors and physical factors are effective in mobilizing bank resources, respectively. Implications: The results of this study can be used to increase the quality of mobilization which directly affects the profitability of resources. Also this research can help other banks to absorb the financial resources and increases the level of invest in the banks. In addition it can help banks to improve their loan paying. Novelty: This research has focused on the large number of factors which can affect mobilization of bank resources which other previous researches have not addressed all these factors together. No other previous researches have focused on the strategies of fundraising, but in this research this goal has been focused.